Artificial Intelligence Algorithms and Techniques in the computation of Player-Adaptive Games. (January 2020) - Ranjitha, M; Nathan, Kazaka; Joseph, Lincy
Abstract: A game usually used as a synonym for entertainment also serves as an educational tool. Originally targeting the enjoyment, the meaning of the game has evolved to much greater conceptions and applications. Games require physical or mental or sometimes both the simulation. Many games help develop practical skills, serve as a form of exercise, or otherwise perform an educational, simulation, or psychological role. Having to be built on some key elements, which are goals, rules, challenge, and interaction. Various strategies and algorithms such as path finding and decision trees, have been developed to simulate those interactions between the human user and the computer in front of him. In video games, artificial intelligence (AI) is used to generate responsive, adaptive or intelligent behaviours primarily in non-player characters (NPCs) similar to human-like intelligence. This paper makes a short analysis of those preferred techniques and suggest from the study and the outcomes, the efficiency of each. The paper also focuses on the heuristic function, implementation platforms and design guidelines of the various searching algorithms used in adaptive games.